Practical guide to hydrogenated nitrile butadiene rubber technology - Keller, Robert (Smithers Rapra, 2012)
Hydrogenated Nitrile Butadiene Rubber (HNBR) is a synthetic polymer that results from the hydrogenation of Nitrile Rubber (NBR). It is widely known for its physical strength and retention of properties after long-term exposure to heat, oil, and chemicals. The unique properties attributed to it have resulted in wide adoption of HNBR in automotive, industrial, and assorted, performance-demanding applications. This practical guide covers everything from the manufacture of HNBR to processing in the finished part production facility. This book forms a complete guide for the practicing rubber formul.